Aesthetic creation theory and landscape architecture. Issue 1 (2nd January 2016) - van Etteger, Rudi; Thompson, Ian H.; Vicenzotti, Vera
Abstract: In recent decades the landscape architectural discourse has tended to eschew ideas of aesthetics while focusing instead on notions of functional and sustainable design. We offer the view that Aesthetic Creation Theory, whose principal exponent is the philosopher Nick Zangwill, has the potential to redress this imbalance by interpreting landscape architecture as 'art'. Zangwill's account of 'art' differs, however, from many other definitions found in philosophical aesthetics: it holds that works of art have aesthetic functions that are essential to them, but also allows that they have other, non-aesthetic functions, for example practical or ecological ones. It thus removes the strict distinction between fine art and the useful arts. After introducing Zangwill's theory, we discuss some rival theories of art and then explore the virtues of Aesthetic Creation Theory for the theory, practice, and pedagogy of landscape architecture.